LIQUID IMMISCIBILITY IN CARBONATE-SILICATE SYSTEMS: REVISION OF EXPERIMENTAL DATA - Anfilogov V.N.; Purtov V.K. (My University, 2003)
Systematic analysis of phase equilibria near the liquidus of silicate-carbonate systems indicates that silicates and carbonates are structurally compatible components and should mix within broad limits when in the molten state. Methodical difficulties in the experimental study of phase equilibria in silicate-carbonate systems are caused by the limited capabilities of the chill method, when components do not pass into the vitreous state. The systems analyzed in this study are demonstrated to have been erroneously characterized by liquid immiscibility, with the structural features arising during their chilling caused not by liquid immiscibility but by the crystallization of carbonates in a rapidly cooling homogeneous melt.